Evaluation of photothermal properties for absorption of solar energy by Co3O4 nanofluids synthesized using endophytic fungus Aspergillus nidulans. (February 2020) - Vijayanandan, Ajuy Sundar; Kandath Valappil, Riya Sidhikku; Balakrishnan, Raj Mohan
Highlights: Biosynthesized Co3 O4 nanofluids used for solar energy storage. Empirical evaluation of Co3 O4 nanofluids for solar energy storage was performed. Agreement observed between experimental and analytical result of optical properties. Abstract: An attempt has been made to compare the optical properties of cobalt oxide (Co3 O4 ) nanoparticles using experimental values and theoretical predictions. Optical transmittance of the nanoparticles obtained was higher than 65% in 550–850 nm containing visible spectrum and the experimental results were in accordance with the predictive datum. The absorption coefficient peak observed is close to the predictive value and is present in the visible region of the light. In addition, there was an excellent agreement between theoretical and experimental results in extinction coefficient and refractive index. Besides, this work proposes and validates a novel idea of using Co3 O4 nanofluids to enhance solar thermal conversion efficiency. Co3 O4 nanofluids synthesized using endophytic fungus Aspergillus nidulans isolated from a medicinal plant, Nothapodytes foetida has been used to illustrate the energy storage capacity of nanofluids. Experimental results reveal that Co3 O4 nanofluids have good specific absorption rate (SAR) and better photo-thermal conversion efficiency than water. Nanofluid exhibited a greater temperature gradient than pure water, which is desired. Thus the good absorption ability of Co3 O4 nanofluids for solar energy indicated that it is suitable for direct absorption solar thermal energy systems.